Study on safety assessment methods of gravity anchors based on a simplified mechanical model - Li, Hongru; Yang, Min; Yin, Xiaotao (Frontiers in Earth Science, 2023)
Gravity anchor block is a common kind of ground anchor for suspension bridge, whose bearing depends on its huge body and big gravity. No requirement to stratum, so safety of the anchor block is important for bridge stability. All estimation index, calculating methods and evaluation criterion on gravity anchor block safety are summarized in the paper. Backing on gravity anchor block of Ruili side for Banjinba grand suspension, its anti-overturning, anti-sliding, base stress and deformation safeties are comprehensively evaluated by method suggested by specification (abbrev. SM), simplified mechanical method (abbrev. SMM) done in the paper and finite element method (abbrev. FEM), whose results are compared and analyzed. Reason of error, improved formula and working condition are presented. Main conclusions are as following. (1) Calculating methods of different evaluation indexes done by specifications lack consistence. Moreover, FEM requires good computer skill for designers. So, it has low feasibility in practice. (2) Simplified mechanical method of gravity anchor block safety estimation is submitted in the paper, whose indexes cover systematic and overall, computing formula is simple and speedy, results being relatively conservative and has good practicability. (3) SM, SMM and FEM are all used in safety estimation of gravity anchor block Ruili side. Its anti-overturning & anti-sliding stability coefficients all meet to specification requirements, less than 2.0. SM cann’t estimate base tensile stress under limit condition, SMM denotes tensile stress occurrence when 2.5 times main cable design force done, that of FEM being 3.2P. Deformation calculation methods are not given by SM, which is suggested by SMM on basis of elastic mechanics. Horizontal displacement under design load condition are 122 mm (SMM), 108 mm (FEM), 44 mm (composite foundation treated by root piles), safety standard being less than 80mm. Those of vertical displacement are 338 mm (SMM)、110mm (FEM)、123mm (composite foundation treated by root piles), safety standard being less than 160mm. All these prove feasibility of SMM, which can be used for safety design of the gravity anchor block in lacking regional experience area.